(untitled) - McBride, P.K.; P.K. McBride (London)
Visual Basic is the standard programming language for Windows. Well over a million applications are in commercial use, so anyone who wants to become a Windows expert should master it, and all Windows users should have a grasp of it. Visual Basic has been evolving steadily with each new version offering more features. The current version, Visual Basic.NET is a highly sophisticated language. This book is written for those students from NVQ through to degree level studying on a Visual Basic.NET course. It provides a concise and practical introductory guide. The book introduces the concepts and techniques across a broad front. It then goes deeper into key aspects, bringing in new objects and language elements as needed, using larger and more interesting example programs for illustration
Keywords: Microsoft Visual Basic; BASIC (Computer program language)